Clinical and laboratory evaluation of upper respiratory symptoms in elite athletes - Cox, A. J.; Gleeson, M.; Pyne, D. B.; Callister, R.; Hopkins, W. G.; Fricker, P. A. (Clinical Journal of Sport Medicine, 2008)
Objective: To characterize the etiology of upper respiratory symptoms in elite athletes presenting to a sports physician for treatment.